Extraction and identification of saponins from American agave leaves, and their role as a potential source of phytonutrients with great economic value - Cevallos Gallegos, Polette Katerine (2021)
The Agave americana plant better known as penco or maguey shows a great importance in the traditions of folk groups present along the inter-Andean alley of Ecuador. The best-known products of Agave americana are traditional drinks such as Chaguarmishqui, the production of fibers, as food, and as a source of steroidal saponins. Saponins are secondary metabolites present in the genus agave, which have been investigated for their therapeutic potential as anti-inflammatory, antitumor, antifungal, and antibacterial drugs, drawing the attention of phytochemicals, biologists, and scientists for drug discovery1–3. Based on this, the present thesis aims to demonstrate the presence of steroidal saponins in the leaves of the Ecuadorian subspecies Agave americana L., which are considered as a waste product during the production of Chaguarmishqui. The Agave americana L. leaf was dried and pulverized and prepared hydroalcoholic extracts applying ultrasound-Assisted Extraction (UAE) as an extraction method, these crude extracts were partitioned to obtain extracts of different polarity to which the phytochemical profile and the identification of saponins were carried out using chromatographic and spectroscopic techniques. The phytochemical characterization was positive for saponins and other secondary metabolites, both in the crude extract and in the more polar extracts. Direct acid hydrolysis was carried out to obtain the sapogenins and the phytochemical analysis was positive for glycosides and carbohydrates in the polar fraction, demonstrating that the aglycone was released being in the non-polar fraction, being demonstrated with the results obtained from the liquid chromatography analysis high resolution, infrared spectroscopy, and nuclear magnetic resonance. With the results of this work, it was possible to determine that if there are steroidal saponins in the leaves of Agave americana L. and that they are found in the extracts with the highest polarity when partitioning a hydroalcoholic extract, and the sapogenins could be determined in the extracts of lower polarity when applying acid hydrolysis directly or indirectly.